Pengaruh Ibadah Keluarga dan Pola Asuh Orangtua Terhadap Pemeliharaan Iman Pemuda Gereja Advent di Kebayoran Cabang Lebakwangi - Denny Austin Panjaitan; Rudolf Weindra Sagala; Alvyn C. Hendriks (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to find out, analyze, explore and test the description of family worship and parenting patterns and the maintenance of faith in youth at the Kebaoran Adventist Church, Jakarta. The method used in this article is the library method with a descriptive approach. The results of the study show that a strong church is a church that has members of the congregation standing firm in their faith. Where every generation is present to maintain evangelism in the surrounding area. This generation will not exist if there is no maintenance of good faith, especially the younger generation who are expected to become leaders in the future. Faith maintenance is a process that is expected to occur in the life of every believer. It is also expected to happen in the lives of young people.